PROKRASTINASI AKADEMIK MAHASISWA - ., Luhur Wicaksono (Universitas Tanjungpura, 2017)
Academic procrastination is an academic task delaying behavior with otheractivities that are not so important. Academic procrastination has certain types,features, aspects and effects that mark it. Academic procrastination at a certain level is very detrimental to the students, because it can have an effect on their academic achievement. Academic procrastination that leads to a decline in academicachievement should be immediately assisted for solving its problems in several ways. In this case the counselor is required to play a role to alleviate the students who have the problem.